Relations between pre-service teacher gaze, teacher attitude, and student ethnicity - Keskin, Özün; Gabel, Sylvia; Kollar, Ingo; Gegenfurtner, Andreas (Frontiers in Education, 2023)
In classrooms, ethnic minority students are often confronted with several disadvantages – such as lower academic achievement, more negative teacher attitudes, and less teacher recognition – which are all well examined in educational research. This study sought to understand if more negative teacher attitudes and lower teacher recognition are reflected in teacher gaze. Controlling for student behavior, do teachers look more on ethnic majority than on ethnic minority students? If teachers have a visual preference for ethnic majority students, then we would expect that teachers show a higher number of fixations, longer duration of fixations, and shorter times to first fixation on ethnic majority compared with ethnic minority students. To test this assumption, we designed an explanatory sequential mixed-method study with a sample of 83 pre-service teachers. First, pre-service teachers were invited to watch a video of a classroom situation while their eye movements were recorded. Second, after watching the video, they were asked to take written notes on (a) how they perceived the teacher in the video attended to ethnic minority students and (b) which own experiences they can relate to situations in the video. Finally, a standardized survey measured participants’ age, gender, ethnic background, explicit attitudes toward ethnic minority students, self-efficacy for teaching ethnic minority students, and stereotypes associated with the motivation of ethnic minority students. Results indicated that, in contrast to our hypothesis, pre-service teachers had longer fixation durations on ethnic minority compared with ethnic majority students. In addition, pre-service teachers’ explicit attitudes correlated positively with number (r = .26, p < .05) and duration (r = .31, p < .05) of fixations, suggesting that pre-service teachers with more positive attitudes toward ethnic minority students also looked more and longer on ethnic minority students. Furthermore, qualitative analyses indicated that pre-service teachers associated the disadvantaged situations for ethnic minority students with teachers’ stereotypes and student language difficulties; they also referred to their own ethnic minority when reflecting on specific situations in the video. We discuss these findings considering their significance for teacher education and professional development and their implications for further research on dealing with student diversity.